A Sourcing Strategy for Active Pharmaceutical Ingredients (APIs) - George M. Clarke; K. Peter Schnurrenberger; Bernhard Scholl (CHIMIA, 1998)
We describe the development over the past decade of a sourcing strategy within the Roche group for active pharmaceutical ingredients and the intermediates used in their manufacture. The roles of certain production sites have been modified in the light of this strategy. Before sourcing decisions are taken, criteria including life-cycle phase of the product, whether the step under review comes early or late in the synthesis, protection of proprietary know-how, quantities needed, speed, available capacity and full production costs are systematically evaluated on a case-by-case basis. For each sourcing decision, different scenarios are compared, in particular that of in-house vs. external production. In future, we envisage intensified competition both among Contract Manufacturing Organisations (CMOs) for business from large pharma concerns and among the large pharma concerns themselves for the capacity available from the CMOs. In consequence, the large pharma concerns will have to continually adapt their sourcing strategies to the changing environment and will have to have available flexible production plants and organisations if they wish to maintain a viable in-house alternative to contract manufacture.